2002
DOI: 10.1002/jcb.10159
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide disturbs the subcellular distribution of GABAA receptor in brain neurons

Abstract: Mechanisms underlying the action of acrylamide on neurons were studied by monitoring the expression of GABA(A) receptor (R) in cultured brain neurons derived from chicken embryos. In situ trypsinization of the neurons and 3H-flunitrazepam binding assay were employed to examine the subcellular distribution of GABA(A)R. A 3-h exposure of the cultured neurons to 10 mM of acrylamide raised reversibly the proportion of intracellular (trypsin-resistant) 3H-flunitrazepam binding sites by about 48% and decreased cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…This will lead to increased permeability of the membranes and disturbance of the ion concentration in the cytoplasm and cell organelles. The alterations and irregularity in shape that were found in the acrylamide-treated group could be coincided with the results of some previous studies [24]. Accumulation of sodium leads to an increase in water content in the cell leading to its swelling.…”
Section: Discussionsupporting
confidence: 90%
“…This will lead to increased permeability of the membranes and disturbance of the ion concentration in the cytoplasm and cell organelles. The alterations and irregularity in shape that were found in the acrylamide-treated group could be coincided with the results of some previous studies [24]. Accumulation of sodium leads to an increase in water content in the cell leading to its swelling.…”
Section: Discussionsupporting
confidence: 90%
“…The increase in the rate of tubulin polymerization by ACR may alter the rate of transport of axonal constituents including NF and contribute toward their accumulation in the focal swellings observed in this neuropathy [41]. However, another study revealed that ACR down regulated the MT system as revealed both by immunostained and electron microscopic [38], which was similar to this tubulin result in pellet.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies showed that ACR induces collapse of NFs in human neuroblastoma cells to form perikaryal inclusion bodies [37] and reduction in the numbers of NFs in the perikarya [38]. ACR increased the expression of mRNA for NF-M NF (acute effect) and NF-L (chronic effect) protein sub-units in rat brain [39].…”
Section: Discussionmentioning
confidence: 97%
“…An in vitro study showed that ACR blocks the intracellular transport of the GABAa receptor, resulting in receptor distribution disturbance [11]. In addition, a recent study, using brain synaptosomes, showed that ACR impairs synaptic functions and subsequent decreases in neurotransmitter release [12].…”
Section: Introductionmentioning
confidence: 98%